Função endotelial de pacientes obesos submetidos ao Bypass Gástrico em Y de Roux com e sem Síndrome da Apneia Hipopneia Obstrutiva do Sono - Machado, Ana Cristina de Assunção (2018)
Introduction: Obesity is one of the most important nutritional diseases in the modern world, especially in its abdominal form, where adipose tissue implies a higher cardiovascular risk and is responsible for inflammatory phenomena. Abdominal obesity predisposes to calcification of the coronary arteries and endothelial dysfunction, as well as the occurrence of other comorbidities such as hypertension diabetes and Obstructive Sleep Apnea Hypopnea Syndrome (OSAHS). OSAHS leads to decreased quality of life (QOL) and functional capacity, together with an increased risk of cardiovascular disease, predisposing to higher rates of morbidity and mortality. Objectives: To evaluate the impact of weight loss in the first six months after bariatric surgery on endothelial function in patients with and without obstructive sleep apnea syndrome (OSAHS). Methodology: the sample consisted of 56 patients homogeneously divided into groups without OSAHS (control group) and with OSAHS (OSAHS). All patients were evaluated in the Roux-en-Y Gastric Bypass (RYGB) preoperative period and six months after surgery. OSAHS diagnosis in the preoperative period was performed using instruments validated for apnea tracking and confirmed by polysomnography. The evaluations included anthropometric measurements, electrical bioimpedance, clinical symptoms of OSAHS and endothelial function, through the flow-mediated dilatation (FMD) of the brachial artery. Results: weight loss induced by surgery improved the anthropometric, bioimpedance and endothelial function results in both groups. Patients presented a significant clinical improvement in the symptoms of OSAHS throughout the study. However, patients with OSAHS had an improvement in the endothelial function 2.5% lower (p <0.001) than the control group. Conclusion: this study shows that the presence of OSAHS before bariatric surgery interferes in the clinical picture, interfering in the improvement of endothelial function.